Characterization of Family Farming in the Portal da Amazônia Territory in a Pre-Pandemic Context - Gervazio, Wagner; Sais, Adriana Cavalieri; Christofoletti, Jessica Helena; Oliveira, Renata Evangelista de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
In this paper, we characterized family farming in the Portal da Amazônia territory (TPA) by analyzing family farming as a socio-ecological system. The study was carried out using bibliographical research and secondary data. The data were organized based on four dimensions: ways to occupy the landscape, relationships with the market, social organization, and governance and institutions. In the TPA, there are 19,947 rural enterprises, of which 16,422 are of family farming and 78 are settlement projects of agrarian reform. Pasture occupies 38% of the area and deforestation accounts for 36.6% of it. The gross domestic product is responsible for 5.7 % of the state total. The gross value of temporary crop production corresponds to 4.5% of MT value, while permanent crops account for 16.10%. The commercialization of products is carried out directly to the neighbors, in farmers’ markets and through apps. The population is 282,328 inhabitants, 32% of which living in rural areas. In addition to family farmers, there are nineteen traditional peoples and communities and nine ethnic groups of indigenous peoples. 54% of agricultural enterprises belong to people aged between 45 and 65 years. The infant mortality rate is 16.02. The territory has 249 schools, 93 of which are located in the rural area, comprising 37% of the total schools in the region. There are a large number of civil society organizations working in this area. The territory also relies on PAA, PNAE, and PRONAF. The pre-pandemic scenario indicates weaknesses that characterize family agriculture.